Analysis of spatial correlations between patterns of DNA damage response and DNA replication in nuclei of cells subjected to replication stress or oxidative damage. Issue 10 (30th July 2013) - Bernas, Tytus; Berniak, Krzysztof; Rybak, Paulina; Zarębski, Mirosław; Zhao, Hong; Darzynkiewicz, Zbigniew; Dobrucki, Jerzy W.
<x xml:space="preserve">Abstract</x> Sites of DNA replication (EdU incorporation) and DNA damage signaling (γH2AX) induced by camptothecin (Cpt) or hydrogen peroxide (H2O2) form characteristic patterns of foci in cell nuclei. The overlap between these patterns is a function of the number of DNA double strand breaks (DSBs) formed in replication sites. The goal of this study was to optimize a method of quantitative assessment of a degree of correlation between these two patterns. Such a correlation can be used to estimate a probability of inducing damage in sections of replicating DNA. The damage and replication foci are imaged in 3D with confocal microscopy and their respective positions within nuclei are determined with adaptive image segmentation. Using correlation functions spatial proximity of the resultant point patterns is quantified over the range of distances in cells in early‐, mid‐ and late S‐phase. As the numbers (and nuclear densities) of γH2AX and replication foci differ significantly in the subsequent substages of S phase, the detected association values were corrected for the expected random overlap between both classes of foci. Thus, the probability of their nonrandom association was estimated. Moreover, self association (clustering) of DNA replication sites in different stages of S‐phase of the cell cycle was detected and accounted for. While the analysis revealed a strong correlation between the γH2AX foci and the sites of DNA replication in cells treated with Cpt, only a low correlation was apparent in cells exposed to H2O2. © 2013 International Society for Advancement of Cytometry